Digital heritage for the future - Lusenet, Yola (Cadernos BAD, 2003)
This paper provides an overview of various issues related to digital preservation: the nature of digital information, the roles and responsibilities of institutions, selection of materials and choices in preservation, with many references to current initiatives. It argues that traditional concepts like publication and record have to be redefined in the digital world, in order to develop effective preservation policies. Preservation has become a matter of keeping access rather than keeping objects, for which the first requirement is defining the digital object and its essential characteristics. Documentation has moved to the centre of preservation activities, which now have to take place quite early in the lifecycle of materials.